2019
DOI: 10.1002/aur.2175
|View full text |Cite
|
Sign up to set email alerts
|

Infection and Fever in Pregnancy and Autism Spectrum Disorders: Findings from the Study to Explore Early Development

Abstract: Maternal infection and fever during pregnancy have been implicated in the etiology of autism spectrum disorder (ASD); however, studies have not been able to separate the effects of fever itself from the impact of a specific infectious organism on the developing brain. We utilized data from the Study to Explore Early Development (SEED), a case-control study among 2-to 5-year-old children born between 2003 and 2006 in the United States, to explore a possible association between maternal infection and fever durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
68
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 40 publications
1
68
1
Order By: Relevance
“…Another line of evidence comes from studies of environmental exposures associated with ASD. These include studies associating prenatal exposure to valproate [9], as well as to maternal bacterial [10] and viral infections during pregnancy (i.e., cytomegalovirus (CMV)) [11]. These diverse lines of evidence implicate early cortical development as one major convergent period of risk in the development of ASD.…”
mentioning
confidence: 99%
“…Another line of evidence comes from studies of environmental exposures associated with ASD. These include studies associating prenatal exposure to valproate [9], as well as to maternal bacterial [10] and viral infections during pregnancy (i.e., cytomegalovirus (CMV)) [11]. These diverse lines of evidence implicate early cortical development as one major convergent period of risk in the development of ASD.…”
mentioning
confidence: 99%
“…In the past, it was shown that toll-like receptor 3 (TLR3) signaling triggered by poly(IC) was important to induce IL6 and IL17, which in turn played key roles in placental and brain in ammatory signaling that preceded the onset of ASD-like behaviors [74]. In humans, signi cant immunologic challenge and/or in ammation leading to fever during pregnancy, similar to that produced by poly(IC) in mice, is also known to increase the risk of autism [75,76] and schizophrenia [77].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the lack of association observed between prenatal infections and pervasive development disorders, which was replaced by ASD in the DSM-V (American Psychiatric Association, 2013), should be noted, as it contradicts a large body of evidence suggesting the contrary (Jiang et al, 2016). Complementary evidence (Croen et al, 2019) has, however, suggested that it may not be the infectious agents themselves which are associated with abnormal neurodevelopment, but rather the accompanying immune activation, relating to side attributes such as fever. This aligns with findings from studies reporting links between prenatal levels of biomarkers such as inflammatory cytokines and increased odds of ASD in offspring (Goines et al, 2011;Abdallah et al, 2013;Zerbo et al, 2016).…”
Section: Discussionmentioning
confidence: 99%